1 Proceedings and Acts of the General Assembly of Maryland 347 (William Hand Browne ed., 1883) - (:unkn) unknown (My University, 1654)
All persons from 16 yeares of age to Sixty shall be provided with Serviceable Armes & Sufficient Amunition of Powder and Shott ready upon all occasions.